Determination The Internet of Things: Technological Innovation, Corporate Culture, and Computer-Based Information Systems - Isnawati, Isnawati; Ali, Hapzi (Siber International Journal of Digital Business (SIJDB), 2023)
Determination of the Internet of Things: Technological Innovation, Corporate Culture, and Computer-Based Information Systems. This analysis reviews published works on the subject of ESSB. In order to provide a foundation for future research, this article aims to generate hypotheses regarding the correlations between variables. Academic databases such as Google Scholar, Mendeley, and others are part of the research objects. This study employs a literature review strategy based on the use of publicly accessible electronic resources, such as e-books and journals. A descriptive qualitative analysis is used. The findings of this analysis are as follows: 1) Technological Innovation Determines the Internet of Things; 2) Corporate Culture Determines the Internet of Things; 3) Computer-Based Information Systems Determine the Internet of Things.